2020
DOI: 10.1094/phyto-03-20-0073-r
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Wheat Blast Resistance Gene Rmg8 in Bangladesh Suggested by Distribution of an AVR-Rmg8 Allele in the Pyricularia oryzae Population

Abstract: Wheat blast caused by the Triticum pathotype of Pyricularia oryzae was first reported in 1985 in Brazil and recently spread to Bangladesh. We tested whether Rmg8 and RmgGR119, recently identified resistance genes, were effective against Bangladeshi isolates of the pathogen. Common wheat accessions carrying Rmg8 alone (IL191) or both Rmg8 and RmgGR119 (GR119) were inoculated with Brazilian isolates (Br48, Br5, and Br116.5) and Bangladeshi isolates (T-108 and T-109). Br48, T-108, and T-109 carried the eI type of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 22 publications
3
20
0
Order By: Relevance
“…S11). B71 lineage isolates also lack the PWT4 effector, which is known to suppress AVR-Rmg8-elicited resistance (Horo et al 2020;Inoue et al 2021). These genome analyses predict that the B71 lineage isolates (AVR-Rmg8 positive, PWT4 negative) cannot infect wheat plants with the matching disease resistance gene Rmg8.…”
Section: Main Textmentioning
confidence: 94%
See 1 more Smart Citation
“…S11). B71 lineage isolates also lack the PWT4 effector, which is known to suppress AVR-Rmg8-elicited resistance (Horo et al 2020;Inoue et al 2021). These genome analyses predict that the B71 lineage isolates (AVR-Rmg8 positive, PWT4 negative) cannot infect wheat plants with the matching disease resistance gene Rmg8.…”
Section: Main Textmentioning
confidence: 94%
“…S11). B71 lineage isolates also lack the PWT4 effector, which is known to suppress AVR-Rmg8-elicited resistance (Horo et al 2020; Inoue et al 2021).…”
Section: Main Textmentioning
confidence: 99%
“…So far, genetic studies on WB resistance have been mostly limited to elite germplasm, hence there is a need to investigate landraces, synthetic wheat and wild relatives for novel sources/genes for WB resistance. A good example is the landrace GR119 [23] which is a novel resistance source against WB and carries two genes Rmg 8 and Rmg GR119 for WB resistance. Identifying novel MTAs using non-2NS genotypes is suggested for future GWAS studies to avoid their effects being masked by 2NS translocation.…”
Section: Discussionmentioning
confidence: 99%
“…Other genes like Rmg1, Rmg 4, Rmg 5 and Rmg 6 are resistant against non-MoT strains of M. oryzae [19][20][21]. The gene Rmg 8 in combination with Rmg GR119 confers good resistance to MoT isolates from Brazil and Bangladesh at the heading stage primarily in controlled environments, implying their promising utilization in breeding programs [16,[22][23][24]. Apart from the Rmg genes, QTL mapping and genome-wide association studies (GWAS) have also identified numerous QTLs and marker trait associations (MTAs) on various wheat chromosomes.…”
Section: Introductionmentioning
confidence: 99%
“…Air temperatures greater than 26°C and the genetic variability of the blast population observed in more aggressive Triticum lineage races had been the most important factors negatively affecting the genes' effectiveness. Therefore, durable and effective resistance is yet to be sourced and incorporated into commercial materials (Takabayashi et al 2002;Hau et al 2007;Zhan et al 2008;Nga et al 2009;Tagle et al 2015;Anh et al 2015Anh et al , 2018Cruz et al 2016b;Wang et al 2018;Asuke et al 2019Asuke et al , 2021Horo et al 2020;Jiang et al 2020;Inoue et al 2021;Dianese et al 2021). The efficiency of the photosynthetic apparatus affected the blast resistance response on one wheat commercial line moderately resistant and another one susceptible.…”
Section: Wheat Blast Managementmentioning
confidence: 99%